AB0692 ASSESSING RECOVERY TIME AFTER COLD CHALLENGE AND THUMB INVOLVEMENT CAN HELP TO RULE OUT SYSTEMIC SCLEROSIS IN PATIENTS PRESENTING WITH RAYNAUD'S PHENOMENON. (June 2019) - Roon, Anniek van; Roon, Arie Van; Stel, Alja J.; Bootsma, Hendrika; Smit, Andries; Mulder, Douwe J.
Abstract : Background: Distinguishing primary Raynaud's phenomenon (PRP) from Raynaud's phenomenon secondary to systemic sclerosis (SSc) is crucial in the early detection of SSc. Recently we reported that patients with more severe vasculopathy suffer from a prolonged ischemia time during Raynaud's attack. [1] additionally, it appears that the thumb is more frequently involved in SSc, where it seems to be spared in PRP. [2] these two characteristics are easily recognized by patients and physicians, and can help rising awareness for SSc. Objectives: The aim was to study if the recovery of a Raynaud's attack and involvement of the thumb are differentiators for SSc in patients with Raynaud's phenomenon (RP). Methods: A stepwise cooling and recovery procedure was performed, provoking an RP attack, in patients with PRP and SSc. One hand was submerged up till the radiocarpal joint in water. The water temperature was lowered in steps of 3 degrees Celsius every four minutes, from 33 until at least 9 degrees Celsius. Afterwards ten minutes of recovery in room air of 23 degrees Celsius was observed. During the procedure perfusion of the fingertips was assessed by photo-electric plethysmography. Results: In total 18 patients with SSc and 68 patients with PRP underwent the procedure. Seventeen (94%) SSc patients had no restoration of perfusion after ten minutes in one or more fingers, compared to 28 (41%) PRP patients (figure 1 ), with a negative predictive value of 98%. During cooling, 17 (94%) SSc patients developed abnormal perfusion in the thumb compared to 48 (71%) PRP patients (p=0.036), with a negative predictive value of 95%. There was no difference in involvement of the other fingers during cooling (all p>0.05). Positive predictive values were low. Conclusion: In patients with RP, when there is restoration of perfusion in all fingers after ten minutes or when the thumb is spared, the presence of an underlying SSc is very unlikely. Although this objective measurement needs to be verified with patient's reports, these results suggest that these simple signs can help physicians to assess if the patient needs to be referred for additional tests. References: [1] van Roon aM, Smit aJ, van Roon aM, Bootsma H, Mulder DJ. Digital ischaemia during cooling is independently related to nailfold capillaroscopic pattern in patients with Raynaud's phenomenon. Rheumatology (Oxford)2016;55:1083-1090. [2] Chikura B, Moore T, Manning J, Vail a, Herrick aL. Thumb involvement in Raynaud's phenomenon as an indicator of underlying connective tissue disease. J Rheumatol2010;37:783-786. Disclosure of interests: Anniek van Roon: None declared, arie Van Roon: None declared, alja J. Stel: None declared, Hendrika Bootsma Grant/research support from: Unrestricted grants from Bristol-Myers Squibb and Roche, Consultant for: Roche, Bristol-Myers Squibb, Novartis, Medimmune, Union Chimique Belge, Speakers bureau: Bristol-Myers Squibb, Novartis, andries Smit Shareholder of: Has been co-founder, and is still shareholder of Diagnoptics Technologies, the company which developed the aGE reader., Douwe J Mulder Grant/research support from: My University has received research grants for my research from: Boehringer ingelheim and actelion, Speakers bureau: My University has received speakers fee from: Sanofi